Maqāṣid Al-Syarī‘Ah Sebagai Basis Perlindungan Perempuan Dari Kekerasan - Puspa Devi, Chindya; Aminuddin, Aminuddin (Fakultas Syariah IAI Muhammadiyah Bima, 2025)
Violence against women remains a pressing humanitarian problem at both the global and national levels, with complex impacts encompassing physical, psychological, social, and even spiritual dimensions. From an Islamic perspective, this issue cannot be addressed solely through a normative approach but requires a contextual framework aligned with the universal objectives of the Sharī‘ah. This study seeks to examine the role of Maqāṣid al-Sharī‘ah as both a theoretical and practical foundation for providing protection to women from various forms of violence, particularly through the lens of Jasser Auda. The research method employed is normative-juridical with a qualitative-descriptive approach, utilizing the analysis of classical and contemporary Islamic legal literature, national regulations, and international legal instruments. The findings indicate that acts of violence against women constitute a fundamental violation of the five essential principles of Maqāṣid, namely ḥifẓ al-dīn (protection of religion), ḥifẓ al-nafs (protection of life), ḥifẓ al-‘aql (protection of intellect), ḥifẓ al-nasl (protection of lineage), and ḥifẓ al-māl (protection of property). Furthermore, Jasser Auda’s systemic approach, with its six features—cognition, purposefulness, holism, openness, multidimensionality, and teleology—provides a dynamic and applicable analytical framework for creating a just and equitable system of women’s protection. In this regard, Maqāṣid al-Sharī‘ah functions not only as a normative framework within Islamic law but also as an ethical and practical paradigm capable of strengthening policies, regulations, and public awareness in efforts to eliminate violence against women.